Strategi dan Evaluasi High Order Thingking Skill HOTS dalam Pembelajaran PAI (Studi Kasus di SMAN 114 Jakarta) - Muhammad Ghufron Iqbal; Siti Uswatun Khasanah; Attabik Luthfi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to determine the learning strategies and evaluation of Islamic Religious Education (PAI) based on Higher Order Thinking Skills (HOTS) at SMAN 114 Jakarta. This research uses a qualitative descriptive analysis approach. The subjects of this study were Islamic Religious Education (PAI) teachers and class XI IPS students at SMAN 114 Jakarta. Data collection techniques used were observation, interviews, and documentation. The results showed that the PAI learning strategy based on HOTS implemented at SMAN 114 Jakarta was quite good, but still needs to be improved. PAI teachers have used various learning methods that can improve students' HOTS, such as discussions, questions and answers, and problem solving. However, PAI teachers still need to increase the use of learning media that is more varied and interesting. In addition, PAI teachers also need to improve their ability to provide effective feedback to students. Evaluation of PAI learning based on HOTS at SMAN 114 Jakarta has been carried out regularly, but still needs to be improved. PAI teachers have used various assessment instruments that can measure students' HOTS, such as written tests, oral tests, and project assignments. However, PAI teachers still need to increase the use of assessment instruments that are more authentic and contextual.